Förderung von Werbekompetenz bei Kindern: Bestandsaufnahme medienpädagogischer Materialien. Medienimpulse - Friedrichs, H.; Kröger, S.; Meister, Dorothee M.; Sander, U.

Kinder und Werbung. Eine Evaluation von Projekten Förderung von Werbekompetenz von Kindern - Friedrichs, H.; Kröger, S.; Meister, Dorothee M.; Sander, U.

«‹Neu lernen ist leichter als umlernen›: Über die Schwierigkeiten einer bildungsgewohnten Gruppe, neue (mediale) Partizipationsformen aufzubauen.» - Kamin, Anna-Maria; Meister, Dorothee M.

Potenziale von Web 2.0-Technologien für die Schule - Magenheim, J.; Meister, Dorothee M. (Schule in der digitalen Welt. Medienpädagogische Ansätze und Schulforschungsperspektiven)

Der Einsatz digitaler Medien als Herausforderung von Schule - eine Annäherung - Albers, C.; Magenheim, J.; Meister, Dorothee M. (Schule in der digitalen Welt. Medienpädagogische Ansätze und Schulforschungsperspektiven)

Sozialität und Strukturen innerhalb von Social Network Sites. Theoretische und empirische Bezüge - Meise, B.; Meister, Dorothee M. (stream your life!?)

Virtuelle Hochschule – Zum Alltag des Lehrens und Lernens aus medienpädagogischer Sicht - Meister, Dorothee M. (Baustelle Informationsgesellschaft und Universität heute)

An Easy Extendable Modeling Framework for Discrete Event Simulation Models and their Visualization - Renken, Hendrik; Laroque, Christoph; Fischer, Matthias (Proceedings of The 25th European Simulation and Modelling Conference - ESM2011)

Parallel Out-of-Core Occlusion Culling - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm
We present a parallel rendering system for PC-Clusters to visualize large 3D scenes. One single visualization node, equipped with a high-end graphics adapter, is supported by a group of backend nodes with weak graphics performance. The objects of the scene are distributed among these backend nodes, they serve two purposes: First, they provide an out-of-core memory system for the visualization node. Second, they assist the visualization node's rendering by performing visibility calculations and only sending visible objects to the visualization node. In order to obtain fast rendering with our system, we have to distribute the objects among the backend nodes in a way that does not only guarantee an even distribution of the objects, but also an even distribution of the visibility calculations and the amount of data send to the visualization node. We identify necessary properties of the distribution and argue that a random distribution is a good candidate. Further, in order to reduce the number of objects sent to the visualization node per frame, we employ an approximate hierarchical occlusion culling in each backend node. For this, they are equipped, in addition to the objects assigned to them, with simplified versions of the other objects of the 3D scene. The visualization node is equipped with 512 MiB video memory and supported by 15 backend nodes. This system is able to render a approx. 350 million polygons (approx. 8.5 GiB) large aircraft model between 20 - 30 fps and thus allows a walkthrough in real-time.

Scenarios, Research Issues, and Architecture for Ubiquitous Sensing - Kanter, Theo; Kardeby, Victor; Forsström, Stefan; Walters, Jamie (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Considerate Equilibrium - Vöcking, Berthold; Hoefer, Martin; Skopalik, Alexander; Penn, Michal; Polukarov, Maria (IJCAI 2011, Proceedings of the 22nd International Joint Conference on Artificial Intelligence,)

Mechanical and Physical Properties - A Way to asses quality of Laser Sintered Parts - Rüsenberg, Stefan; Schmidt, L.; Schmid, Hans-Joachim (22th Annual International Solid Freeform Fabrication Symposium)
The aim of this paper is the description and evaluation of physical properties like porosity and density and their influence on mechanical properties of laser sintered polyamide parts. For example, by reducing the porosity an increase of mechanical properties is possible. The correlation of laser parameters to these properties is investigated in detail. The energy density is an important parameter for the laser sintering process. By changing laser power, scan velocity and hatch distance an influence on manufactured components is given. A systematic variation of all three laser parameters is performed. A comparison of results obtained at constant energy densities obtained by varying these relevant parameters accordingly is shown as well.

Porosity as a key to increase material properties of laser sintered parts - Rüsenberg, Stefan; Schmidt, L.; Hosse, H.; Schmid, Hans-Joachim

Direct Manufacturing Design Rules - Adam, Guido; Zimmer, Detmar

Steigerung der Anlagenverfügbarkeit von Antriebssystemen durch methodische und modulare Konzeption. Modulare Konzeption von als Einzelstücke oder in Kleinserien hergestellten Antriebssystemen mit großer Nennleistung - Fiekens, Nicolas; Zimmer, Detmar (VDI/VDE-Tagung mit Fachausstellung Antriebssysteme 2011. Elektrik, Mechanik und Hydraulik in der Anwendung)

DMDR Direct Manufacturing Design Rules. Erarbeiten von applikationsunabhängigen Konstruktionsregeln - Zimmer, Detmar; Adam, Guido (Rapid.Tech 2011 Fachmesse und Anwendertagung für Rapid-Technologie)

Bestimmung der Biegesteifigkeit eines Schubgliederbandes - Zimmer, Detmar; Möller, Jens (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Hybrid Planning for Self-Optimization in Railbound Mechatronic Systems - Adelt, Philipp; Esau, Natascha; Hölscher, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Zimmer, Detmar

Component-Based Hazard Analysis for Mechatronic Systems - Priesterjahn, Claudia; Sondermann-Wölke, Christoph; Tichy, Matthias; Hölscher, Christian (14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

MID-Marktanalyse: Schwerpunkte und Chancen von MID - Franke, Joerg; Dumitrescu, Roman; Gausemeier, Jürgen; Goth, Christian (Sonderausgabe Räumliche elektronische Baugruppen, Fachzeitschrift Elektronik)